Strategic Governance Management in Enhancing Digital Literacy in West Tanjung Jabung Regency's Educational Institutions - Wahyudi, Agung; Nugroho, Marno (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This research aims to analyse the strategy of the Education and Culture Office of Tanjung Jabung Barat Regency in improving digital literacy through the Education Innovation and Good Corporate Governance (GCG) approach. Materials and methods: Data were collected through in-depth interviews, field observations and documentation studies of education digitisation policies and practices. The results show that the strategies implemented include improving teachers' competencies through technology-based training, strengthening digital infrastructure, developing online learning platforms, and applying GCG principles such as transparency, accountability and public participation. In addition, blended learning methods and the utilisation of big data and AI in learning evaluation are also part of the educational transformation. Results: The results show that the strategies implemented include improving teachers' competencies through technology-based training, strengthening digital infrastructure, developing online learning platforms, and applying GCG principles such as transparency, accountability and public participation. In addition, blended learning methods and the utilisation of big data and AI in learning evaluation are also part of the educational transformation. Despite facing challenges such as limited infrastructure and digital literacy, this strategy shows significant potential in improving access and quality of learning, especially in remote areas. Conclusions: The integration of education innovation and good governance principles is key in realising an adaptive and sustainable education system in the digital era. The success of this strategy requires long-term commitment and regulatory support that is flexible to technological dynamics.